2016
DOI: 10.1515/aoas-2015-0041
|View full text |Cite
|
Sign up to set email alerts
|

Is mare milk an appropriate food for people? – a review

Abstract: the use of equid milk in human nutrition is a very interesting research topic in relation to the specific characteristics of this drink. Mare's milk has a composition similar to human milk and is well digested, so it is a perfect alternative to cow's milk in the feeding of children who are allergic to cow's milk. Equid milk's low content of α-lactalbumin and β-lactoglobulin makes it appropriate for such children. Its high concentration of lactose allows for a better growth of intestinal microflora. Mare's milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
84
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 24 publications
2
84
1
4
Order By: Relevance
“…According to literature data ( Jaworski et al 1982;Mirowski and Didkowska 2015;Pieszka et al 2016), the content of different fatty acids in the fat of mare's milk varies. Pietrzak-Fiecko et al (2009b) reported differences between the content of fatty acids in milk fat from mares of various breeds.…”
Section: Original Papermentioning
confidence: 99%
See 4 more Smart Citations
“…According to literature data ( Jaworski et al 1982;Mirowski and Didkowska 2015;Pieszka et al 2016), the content of different fatty acids in the fat of mare's milk varies. Pietrzak-Fiecko et al (2009b) reported differences between the content of fatty acids in milk fat from mares of various breeds.…”
Section: Original Papermentioning
confidence: 99%
“…The highest concentration of proteins was found in milk from the female Hucul Pony (1.85%) and the lowest in that from the Polish Konik (1.15%). The qualitative composition of milk is affected by the parity and phase of lactation (Fuentes et al 1993;Pagliarini et al 1993;Dankow et al 2006;Pecka et al 2012;Mirowski and Didkowska 2015;Pieszka et al 2016). During the lactation phase, the composition of mare's milk adapts to the growing foal's needs for different nutrients (Tomczynski et al 1999;Pieszka and Kulisa 2005;Mirowski and Didkowska 2015).…”
Section: Original Papermentioning
confidence: 99%
See 3 more Smart Citations